Micah Alhadeff: capstone - Alhadeff, Micah, artist (Colorado State University. Libraries, 2022)
The artist's statement: As a graphic designer and digital artist, my work explores the fragmentation and deconstruction of the human body within the digital landscape. I aim to visualize the structural qualities and characteristics of the digital body and understand how these bodies exist within a purely digital framework.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design